Impact of Left Atrial Ablation on the Atrial Contractile Function: Insights From Intracardiac Echocardiography and Electroanatomical Mapping in Persistent Atrial Fibrillation Ablation - Kazuki Noda; Shinichiro Sunamura; Masahiro Suzuki; Kazuyuki Shibutani; Atsushi Tanita; Tsuyoshi Ogata; Toru Takii; Ryoichi Ushigome; Yuji Wakayama; Koji Kumagai; Shigeto Namiuchi (Journal of Arrhythmia)
ABSTRACT Background A left atrial (LA) posterior wall isolation (PWI) is a common additional strategy for persistent atrial fibrillation (PeAF) ablation; yet its impact on the LA function remains unclear. Objective This study aimed to evaluate the effect of the PWI on the LA contractile function using intracardiac echocardiography (ICE). Methods Patients who underwent catheter ablation of PeAF were categorized into extensive encircling pulmonary vein isolation (EEPVI) and PWI groups. The LA contractile function was assessed using the PV reversal wave (PVa) velocity measured by ICE. Results No significant difference in the PVa velocity was observed between the EEPVI and PWI group. The EEPVI group patients were categorized into four groups based on scar extent: low‐scar, anterior wall (AW)‐scar‐only, posterior wall (PW)‐scar‐only, and both walls‐scarred. Compared to the low‐scar group, the both walls‐scar group had significantly lower PVa velocities; though no significant difference was found compared to the PW‐scar‐only group. The PVa velocity had a significant correlation with the AW scar. Furthermore, all patients enrolled in this study were also categorized into four groups based on the scar presence, similar to the previous study. Compared with the low‐scar group, the PVa velocities were significantly lower in the AW‐scar‐only and both walls‐scar groups; however, there was no significant difference in the PW‐scar‐only group. The PVa velocity was significantly correlated with the AW scar. Conclusion An LA PWI did not significantly impair the LA contractile function. AW scarring appeared to have a greater impact on the LA contractility than the PWI or scarring.